THE IMPACT OF PEPTONE-INDUCED HYPERTHERMIA ON FETAL ANOMALIES IN WHITE MICE (MUS MUSCULUS) - ALEN, YOHANNES; NASIF, HANSEN; ASRI, MEISYA DWI; DILLASAMOLA, DWISARI (International Journal of Applied Pharmaceutics, 2025)
Objective: Hyperthermia is an increase in body temperature above 37.5 °C, which can be caused by environmental factors such as infections that disrupt hypothalamic thermoregulation and trigger a rise in body temperature. Methods: The aim of this study was to assess the impact of hyperthermia on fetal anomalies in white mice using 10% peptone as the inducer. The study involved 15 white mice divided into three groups. Peptone 10% was administered to two treatment groups, with the administration time divided into two phases: group 1 on days 3-7 of mouse pregnancy and group 2 on days 8-12 of mouse pregnancy. Parameters observed included maternal weight gain, number of fetuses, and fetal weight analyzed using one-way Analysis of Variance (ANOVA) test, as well as morphological and skeletal abnormalities analyzed descriptively through photographs. Results: The average initial temperature of the female mice in the control group, group 1 and group 2 was 35.4 °C, 35.7 °C, and 35.8 °C, respectively, while the average final temperature of the female mice in the control group, group 1 and group 2 was 35.4 °C, 38.0 °C, and 37.9 °C, respectively. The results showed no significant differences in maternal weight gain and number of fetuses between the treatment group and the control group (p>0.05). However, there was a significant difference in fetal weight between the treatment group and the control group (p<0.05). Descriptive observations revealed anomalies in fetuses fixed with Bouin's solution, including resorption sites, delayed growth, and hemorrhage. In contrast, fetuses fixed with alizarin red showed defects in the 14th rib, metacarpal, and metatarsal bones. Conclusion: Based on these findings, it is concluded that hyperthermia can affect fetal anomalies in white mice.